UJI SINERGISITAS ANTIOKSI DAN EKSTRAK KLOROFORM DAUN TEH (Camellia Sinensis) DENGAN -TOKOFEROL MENGGUNAKAN PENDEKATAN KEMOMETRI - Is Fatimah; Jaka Nugraha (Jurnal Ilmiah Farmasi, 2004)
ABSTRACTAim of this research is to know factor influenced to antioxidative activity of chloroform extract oftea leaf ( Camellia sinensis) with -tocopherol in peanut oil system. Research was done by takedata of peroxide value, tiocyanic acid value dan barbituric acid value of the system addedantioxidant at various concentration. Variance analysis was investigated to the data by interpretingfactors consist of time, extract concentration and -tocopherol concentration followed bydetermination of regression model. Result showed that time, extract concentration and -tocopherolconcentration influence to the antioxidative activity and there was interaction effect of the factors.Optimum condition gained at time of 60 minutes, -tocopherol concentration of 110 ppm andextract concentration of 100 ppm. The model resulted from this analysis can be used to predictsynergistic effect between chloroform extract of tea leaf with -tocopherol.Key word: antioxidant, synergistic effect, extraction